Electrospun Cellulose Acetate/Poly(Vinyl Alcohol) Nanofibers Loaded with Methyl Gallate and Gallic Acid for Anti-Staphylococcus aureus Applications - Pimsumon Jiamboonsri; Weradesh Sangkhun; Sompit Wanwong (Polymers, 2024)
material.
Keywords: Electrospun Nanofibers in Biomedical Applications; Silk-based biomaterials and applications; Coconut Research and Applications